Menganalisis Ayat Tentang Taat dan Patuh kepada Pemimpin - Aditya Nanda Saputra,; Astri Wulansari,; Meinajwa Akbar, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the concepts of obedience and leadership in Islam, referring to verses 59 and 83 of the Quran, and verse 48 of the Quran. The study employed a qualitative-descriptive approach through library research, drawing on classical commentaries, including the Tafsir al-Qurṭubi, the Tafsir Ibn Kathir, and the Tafsir al-Misbah. This research also included contemporary commentaries and scholarly articles from the past five years. The results of the study indicate that obedience to leaders (ulil amri) is conditional, meaning it only applies if leadership is exercised based on the principles of justice, trustworthiness, and the supremacy of God's law. The verses studied also emphasize the urgency of moral responsibility and caution in conveying information as a manifestation of adherence to the values ​​of truth and justice. In the modern context, these principles are relevant to the challenges of the digital era, particularly in addressing disinformation and the crisis of moral authority. Thus, ideal leadership in Islam demands a balance between societal obedience and the moral integrity of the leader, with the law of Allah and the Prophet as the ultimate foundation for all decision-making.